555. Effectiveness of a Treatment Team on Adherence to Health System Guidelines for Hydroxychloroquine Use During Two Phases of the COVID-19 Epidemic. (31st December 2020) - Viehman, J Alex; Nguyen, M Hong; Garner, Will; Apostolopoulou, Anna; Harris, Gavin H; Lucas, Aaron; Jagadeesan, Vidya; Butler, Sharlay; Rapinski, Glen J; McCreary, Erin K; Arbulu, Ricardo; Ganchuk, Steven; et al.
Abstract: Background: Our hospital system created system guidelines to standardize care across 24 hospitals for COVID-19 treatment during the pandemic. Guidelines changed over time. Hydroxychloroquine (HCQ) was unrestricted during phase 1, then restricted by pharmacy outside of a randomized clinical trial (RCT) during phase 2 (excepting those ineligible for RCTs). Methods: This was a prospective study to assess system-wide adherence to COVID-19 treatment guidelines, and to evaluate patient outcomes. Results: Of 261 patients, median age was 67 years (IQR 56–76); 49% (129/261) were male, and 45% (118/261) required ICU care. Overall, 47% (122/261) were in phase 1; HCQ was offered to 57% (69/122) during this phase. The rate of HCQ prescription in phase 2 decreased significantly to 10% (14/136), (p < 0.001). Adherence to COVID-19 treatment protocol was 97% (135/139) during phase 2. Mortality was similar in both phases (22% vs 28%, p=0.32), as was median length of stay (8 vs 7 days, p=0.3). Overall 66 patients (25%) died in the hospital; neither non-adherence (p=1) to system guidelines nor receipt of HCQ (p=0.17) were risk factors for death. Independent predictors of mortality included: new renal replacement therapy (OR 61, 95%CI 6.7–560, p < 0.001), mechanical ventilation (OR 4.9, 95%CI 2.0–11, p < 0.001), abnormal chest X-ray (OR 4.3, 95%CI 1.4–12.6, p =0.009), history of heart failure (OR 3.9, 95%CI 1.5–11, p=0.006), lack of fever on admission (OR 3.5, 95%CI 1.7 -7.6, p =0.001), receipt of corticosteroids (OR 2.7 95%CI 1.1–6.6, p=0.026) and increased age (OR 1.07 per year, 95%CI 1.04–1.1, p < 0.001). Bacterial pneumonia occurred in 8% (21/261), more commonly in those who died (p=0.02). Black patients had a higher race-specific death rate (308 vs 197) per 1000 than white patients (p< 0.001). Conclusion: During the COVID-19 pandemic, our health system guidelines and pharmacy restrictions were successful in delivering consistent care across hospitals. Restriction of HCQ for COVID-19 treatment to RCTs reduced its use in phase two. Non-adherence to systemic guidelines was infrequent, and not associated with adverse outcomes. A COVID-19 treatment team of physicians and pharmacists can effectively coordinate therapy across hospitals in the setting of rapidly changing guidelines. Disclosures: J. Ryan Bariola, MD, Infectious Disease Connect (Employee)Mayne Pharma (Advisor or Review Panel member)Merck (Research Grant or Support)